Well-to-Propeller environmental assessment of natural gas as a marine transportation fuel in British Columbia, Canada - Babak Manouchehrinia; Zuomin Dong; T. Aaron Gulliver (Energy Reports, 2020)
This paper examines the environmental impact of Natural Gas (NG) as a transportation fuel, particularly for marine transportation use. The aim is to provide a systematic evaluation of Greenhouse Gas (GHG) emissions in the upstream fuel supply chain of NG fuel in British Columbia (BC), Canada. The recent introduction of Liquefied Natural Gas (LNG) fuel for ferry operations in western Canada presents a major step towards the large-scale adoption of NG as a cleaner and lower-cost fuel. This makes a systematic approach for accurate Lifecycle Assessment (LCA) of GHG emissions for the NG/LNG fuel more important and urgent. An analysis using operation and fuel consumption data from vessels with different engine technologies and types of fuel shows that the diesel cycle NG engine will produce 2% less CO emissions in comparison to the low sulphur petroleum diesel engine, while other NG engine technologies, such as the lean-burn Otto cycle engine or dual-fuel gas engine, will result in 4% higher CO emissions. This study clears doubts on well-to-pump (WTP) NG emissions, supports the wide adoption of NG fuel and promotes further pump-to-propeller (PTP) emission improvements in marine propulsion.
Keywords: 330